Value‐based decision‐making of cigarette and nondrug rewards in dependent and occasional cigarette smokers: An FMRI study. (22nd July 2019) - Lawn, Will; Mitchener, Ludovico; Freeman, Tom P.; Benattayallah, Abdelmalek; Bisby, James A.; Wall, Matt B.; Dodds, Chris M.; Curran, Helen V.; Morgan, Celia J.A.
Abstract: Little is known about the neural functioning that underpins drug valuation and choice in addiction, including nicotine dependence. Following ad libitum smoking, 19 dependent smokers (smoked≥10/day) and 19 occasional smokers (smoked 0.5‐5/week) completed a decision‐making task. First, participants stated how much they were willing‐to‐pay for various amounts of cigarettes and shop vouchers. Second, during functional magnetic resonance imaging, participants decided if they wanted to buy these cigarettes and vouchers for a set amount of money. We examined decision‐making behaviour and brain activity when faced with cigarette and voucher decisions, purchasing (vs not purchasing) cigarettes and vouchers, and "value signals" where brain activity correlated with cigarette and voucher value. Dependent smokers had a higher willingness‐to‐pay for cigarettes and greater activity in the bilateral middle temporal gyrus when faced with cigarette decisions than occasional smokers. Across both groups, the decision to buy cigarettes was associated with activity in the left paracingulate gyrus, right nucleus accumbens, and left amygdala. The decision to buy vouchers was associated with activity in the left superior frontal gyrus, but dependent smokers showed weaker activity in the left posterior cingulate gyrus than occasional smokers. Across both groups, cigarette value signals were observed in the left striatum and ventromedial prefrontal cortex. To summarise, nicotine dependence was associated with greater behavioural valuation of cigarettes and brain activity during cigarette decisions. When purchasing cigarettes and vouchers, reward and decision‐related brain regions were activated in both groups. For the first time, we identified value signals for cigarettes in the brain. Abstract : Little research has investigated neural activity associated with the valuation and purchase of drugs. Here, the paracingulate gyrus, nucleus accumbens and amygdala were activated when cigarettes were purchased; moreover, activity in the left striatum and vmPFC correlated with the value of cigarettes available. Dependent smokers had greater activity in the middle temporal gyrus when making a cigarette decision compared with occasional smokers. Thus, value‐based regions are involved in valuation and purchase of cigarettes and nicotine dependence partially moderates related activity.